2017
DOI: 10.1371/journal.pone.0177793
|View full text |Cite
|
Sign up to set email alerts
|

Survival and prognostic factors for patients with advanced hepatocellular carcinoma after stereotactic ablative radiotherapy

Abstract: ObjectiveTo evaluate the survival outcomes and prognostic factors of patients with advanced hepatocellular carcinoma (HCC) who underwent stereotactic ablative radiotherapy (SABR).MethodsThis retrospective study evaluated patients with advanced HCC who underwent SABR between December 2007 and July 2015. All patients had Barcelona Clinic Liver Cancer stage C disease and Child–Turcotte–Pugh (CTP) class A–B function. In-field control (IFC), overall survival (OS), prognostic factors, and toxicity were evaluated.Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 28 publications
2
18
0
Order By: Relevance
“…Numerous retrospective studies have found SBRT to be safe and effective in both small HCC (<5 cm) (23-28) and large HCC (>10 cm) (29)(30)(31). Two-year LC, progressionfree survival, and OS rates ranged from 44-90% (32,33), 39-48% (24,34), and 24-67% (24,35), respectively. Some of this variability may be explained by variability of characteristics between study populations.…”
Section: Retrospective Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous retrospective studies have found SBRT to be safe and effective in both small HCC (<5 cm) (23-28) and large HCC (>10 cm) (29)(30)(31). Two-year LC, progressionfree survival, and OS rates ranged from 44-90% (32,33), 39-48% (24,34), and 24-67% (24,35), respectively. Some of this variability may be explained by variability of characteristics between study populations.…”
Section: Retrospective Studiesmentioning
confidence: 99%
“…Toxicities included RILD in 10 patients (11.2%), of which 1 was classic RILD and 8 were non-classic RILD, and one met criteria for both types. Two patients went on to die from non-classic RILD (35).…”
Section: Retrospective Studiesmentioning
confidence: 99%
“…However, in case of inoperability, prospective studies on SBRT and SBRT with optional TACE in primary HCC showed promising 18-month and 3-year overall survival rates of 72% and up to 67%, respectively [33,34]. SBRT is even feasible in patients with advanced-stage HCC, with 3-year overall survival (OS) rates of 24.3% and 3-year local control rates of 78.1% [35]. Furthermore, there is increasing evidence that SBRT may even be superior to TACE regarding survival and recurrence, and especially after prior TAE/TACE treatment [36,37].…”
Section: Indications For Radiotherapymentioning
confidence: 99%
“…The clinical outcomes of SBRT for HCC in the previous reports are shown in Table 2. SBRT has been reported to provide 1-, 2-, and 3-year local control rates of 56-100, 53-95, and 51-92%, and 1-, 2-, and 3-year survival rates of 32-100, 55-100, and 21-82% for HCC, respectively [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. Figure 1 indicates the local control and overall survival after SBRT, BED 10 ≥ 75 Gy in ≤10 fractions (e.g., 40 Gy/4 fr), for HCC at our institute.…”
Section: Sbrt For Hccmentioning
confidence: 99%
“…Manifestations of liver SBRT toxicity have fatigue, damage to the liver, gastrointestinal tract and biliary duct, cytopenia, dermatitis, and rib fractures ( Table 2) [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. Adverse events of radiotherapy depend on the treatment site, and the irradiated doses and volume and are categorized into either acute (typically within 3 months of radiotherapy) or late (months to years after radiotherapy), based on their time of onset [55].…”
Section: Adverse Events Of Sbrt For Hcc In Cirrhotic Liver Risk Factmentioning
confidence: 99%